2000
DOI: 10.1034/j.1600-051x.2000.027012889.x
|View full text |Cite
|
Sign up to set email alerts
|

A controlled re‐entry study on the effectiveness of bovine porous bone mineral used in combination with a collagen membrane of porcine origin in the treatment of intrabony defects in humans

Abstract: The results of this study indicate that clinical resolution of intrabony defects can be achieved using a combination of bovine porous bone mineral and an absorbable, porcine derived collagen membrane when employing a technique based on the principles of guided tissue regeneration. The nature of the attachment between the newly regenerated tissue and the root surfaces needs to be evaluated histologically to confirm the presence of new attachment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
97
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 17 publications
23
97
1
1
Order By: Relevance
“…Bio Oss possesses good osteoconductive properties and is well integrated into bone tissue. Results from histological and clinical studies have demonstrated that Bio Oss is very well tolerated and, until now, no allergic reactions related to the material have been reported (Camelo et al 1998;Richardson et al 1999;Camargo et al 2000;Mellonig 2000;Sculean et al 2002). Furthermore, since its supply is unlimited, a donor site is unnecessary.…”
Section: Introductionmentioning
confidence: 93%
“…Bio Oss possesses good osteoconductive properties and is well integrated into bone tissue. Results from histological and clinical studies have demonstrated that Bio Oss is very well tolerated and, until now, no allergic reactions related to the material have been reported (Camelo et al 1998;Richardson et al 1999;Camargo et al 2000;Mellonig 2000;Sculean et al 2002). Furthermore, since its supply is unlimited, a donor site is unnecessary.…”
Section: Introductionmentioning
confidence: 93%
“…Both the examiners recorded similar measurements during a 2 year trial period of cross-checking which ensured the similarity in probing force and method. Gingival tissue consistency may be modified after the placement of graft material in to the defect, which in turn can impede penetration of the periodontal probe causing false positive results (4).…”
Section: Discussionmentioning
confidence: 99%
“…[12] and Mellonig et al . [13] while in the BDX and TISSEEL group, PD reduction was 4.00 ± 1.41 which were similar with the findings of Cortellini et al .…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal regeneration can be achieved by a variety of surgical procedures including bone grafts, bone substitutes, guided tissue regeneration (GTR) or a combination of bone grafts or bone substitutes and GTR. [1]…”
Section: Introductionmentioning
confidence: 99%